The Health Status of Seagrass Beds in the Coastal Waters of Tidore Island City, North Maluku - Ramili, Yunita; Umasangaji, Halikuddin; Sudin, Salwa (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
This research aims at analyzing the condition of seagrass beds on Tidore, Sibu, Tosa and Guraping Village as a basis for determining coastal ecosystem management. This work was carried out from September to October 2022 in the coastal waters of Rum (St. 1), Tosa (St. 2), Sibu (St. 3), and Guraping (St. 4). The data were collected using Quadratic Linear Transect Method. This research revealed 12 species of seagrass with the highest species composition at Rum-St. 1 (11 species) and the lowest at Tosa-St. 2 (4 species). The types of seagrass which have a wide distribution at four stations are Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata and Syringodium isoetifolium. Meanwhile, Cymodocea serrulate, Halophila spinulosa, Thalassodendron ciliatum and Halodule pinifolia have a narrow distribution only found at certain stations. Thalassia hemprichii had the highest species density and cover values of 211.65 ind/m2 and 31.67% respectively. T. hemprichii also had the highest IVI (74,55% - 135,68%) which indicated its important role in the seagrass ecosystem at the four research stations. Generally, the ecological conditions of seagrass beds indicatd a moderate level of species diversity (H'= 1.25 – 1.77) with high species evenness (E= 0.89 – 0.94) and no species dominating (C= 0.19 – 0.32). The health status of seagrass meadows at the four research stations can be categorized as 'healthy' at Station 1 (68.36%) and 2 (65.63%), while the 'less healthy' category was found at Station 3 (47.62%) and 4 (50.24%).